Analysis of the influence of sustainable economic development on environmental quality in West Sumatra - Ramahdani, Lili; Lubis, Amira Husna (Institute of Computer Science (IOCS), 2025)
Economic development aims to improve the welfare of the community, however, this process often has a negative impact on the environment. This research is a Quantitative research with a descriptive approach. In addition, this research also uses quantitative research methods and uses comparative analysis methods. West Sumatra's Environmental Quality Index (IKLH) from 2020 to 2024 is higher than the National IKLH. This indicates that West Sumatra's environmental quality is better than the national average. When Economic Growth decreases, the value of IKLH also decreases. However, per capita income during the study period experienced an increasing trend, but the quality of the environment in 2024 decreased. It can be concluded that sustainable economic development with environmental quality in West Sumatra shows complex dynamics.